Replication, falsification, and the crisis of confidence in social psychology - Earp, Brian D.; Trafimow, David (Frontiers in Psychology, 2015)
The (latest) “crisis in confidence” in social psychology has generated much heated discussion about the importance of replication, including how such replication should be carried out as well as interpreted by scholars in the field. What does it mean if a replication attempt “fails”—does it mean that the original results, or the theory that predicted them, have been falsified? And how should “failed” replications affect our belief in the validity of the original research? In this paper, we consider the “replication” debate from a historical and philosophical perspective, and provide a conceptual analysis of both replication and falsification as they pertain to this important discussion. Along the way, we introduce a Bayesian framework for assessing “failed” replications in terms of how they should affect our confidence in purported findings.